Kesetaraan Gender dalam Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah: Studi Kasus di MIN 1 Banyumas - Maghfirotun Chanasah (JOIN: Journal of Indonesian Education and Learning, 2025)
This study aims to analyze the implementation of gender equality in the implementationof the Merdeka Curriculum at MIN 1 Banyumas. The Merdeka Curriculum promotesthe principles of inclusivity and equality in the learning process, which includesproviding equal opportunities for students regardless of gender. Although policies andthe curriculum support gender equality, challenges in its practical application are stillfound, both in task distribution and students' perceptions. The task distribution, whichis still based on gender stereotypes, such as female students being more often assigned"feminine" tasks and male students being involved in physical tasks, shows the stronginfluence of social norms in society. Additionally, students' perceptions of gender rolesare still influenced by the social views that develop outside of school, which affectstheir choices in activities and career aspirations. Teachers at MIN 1 Banyumas aretrying to change this perception by giving students the opportunity to explore variousroles without being bound by gender norms. However, these changes require timeand continuous support from various parties, including parents and the community.This study concludes that although the implementation of the Merdeka Curriculumprovides a strong foundation for gender equality, the biggest challenge lies in changingsocial perceptions and long-standing habits in society. A holistic approach involvingthe active role of all parties is needed to achieve more effective gender equality in theeducational environment.